The Effect of STAD on Students’ Ability in Writing Descriptive Text of The Eleventh Grade Students at SMK Negeri 1 Siantar - Sidabutar, Rimelni; Lolo Siahaan, Basar; Munthe, Melda Veby Ristella; Damanik, Bernieke Anggita Ristia Damanik (Innovative: Journal Of Social Science Research, 2024)
This research aimed to investigate the effect of the STAD model on students' abilities in writing descriptive texts among grade XI students at SMK Negeri 1 Siantar, based on the theory developed by Robert Slavin. The methodology employed was quantitative, focusing on the population of grade XI students during the academic year 2023/2024. The researcher selected two classes as samples: XI TKJ-1 served as the experimental group with 36 students, while XI TKJ-2 acted as the control group, also consisting of 36 students. The experimental group received instruction through the STAD model, whereas the control group was taught using conventional methods. Data were collected through pre-tests and post-tests administered to both groups. The experimental class achieved a mean pre-test score of 66, while the control class had a mean score of 60. After the intervention, the experimental class's post-test mean score rose to 76, compared to the control class's post-test mean score of 68. To gather data, the researcher utilized tests as instruments. The t-test results showed a value of 4.444, which surpassed the t-table value of 1.677. This outcome indicated that the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected, confirming that the STAD model had a significant effect on improving the writing skills of grade XI students at SMK Negeri 1 Siantar in crafting descriptive texts.